Regulating Near-Space Activities: Using the Precedent of the Exclusive Economic Zone as a Model?. (3rd July 2019) - Liu, Hao; Tronchetti, Fabio
Abstract: The deployment of high-altitude vehicles in near space with the purpose of providing Internet, communication, and other services represents the new frontier of aerospace activities. Near-space operations are attracting growing interest due to their mult-purpose nature and their anticipated high profitability. Despite such positive perceptions, near-space plans are, however, hampered by the uncertain international legal status of near space. Using the precedent of the exclusive economic zone (EEZ), this article suggests a new categorization of the near space as the exclusive utilization space (EUS) and a set of rules to manage its utilization.